Effectiveness of Hydraulic and Hydrologic Parameters in Assessing Storm System Flooding - Basim K. Nile (Advances in Civil Engineering)
Storm sewer systems face many challenges in urban areas, in particular those systems which are old and surpassing their design period. This study has used data from an urbanized, subcatchment covering 360 ha of dead run watershed in the Alkadeer district, Karbala, Iraq. Physically based models, Autodesk Storm and Sanitary Analysis (ASSA) and multiple nonlinear regression (MNLR), were applied. Hydrology data from 1980 to 2013 were inputted and examined over three scenarios. The results indicated that significant increase in peak flooding was produced by an increase in discharge values which may occur through a higher rainfall intensity. The model was examined and new equations were developed that may help us to better understand the hydraulic and hydrologic simulations that are identified as having the potential to better protect the environment against sudden rainfall intensities. The ratio of area of subcatchment to cross-sectional area of a pipe (Ac/Ap), the ratio of slope of subcatchment to slope of a pipe (Sc/Sp), and the ratio of velocity in subcatchment to velocity in a pipe (Vc/Vp) were the most sensitive parameters informing the ratio of runoff discharge of a subcatchment pipe discharge (Qc/Qp). This study suggests that a more effective management of the storm water system under critical circumstances could be achieved by limiting the above parameters and this increases the efficiency of storm water facilities.